2017
DOI: 10.1111/add.13657
|View full text |Cite
|
Sign up to set email alerts
|

Development of the SBIRT checklist for observation in real‐time (SCORe)

Abstract: Background and aims Screening, Brief Intervention and Referral to Treatment (SBIRT) programs have been imple-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…Seventh, we include a range of outcome measures, including patient outcomes, as a quality check 126 , which address weaknesses of many previous implementation studies in this area, which have focussed on provider outcomes, rather than patient outcomes 42 , 43 . Through the use of existing electronic health records, and further to ethical and confidentiality agreements, we anticipate the ability to link individual AUDIT-C scores with consultations within the primary health care centers and hospitalizations within district hospitals, recording diagnosis for both fully and partially attributable alcohol-related conditions 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventh, we include a range of outcome measures, including patient outcomes, as a quality check 126 , which address weaknesses of many previous implementation studies in this area, which have focussed on provider outcomes, rather than patient outcomes 42 , 43 . Through the use of existing electronic health records, and further to ethical and confidentiality agreements, we anticipate the ability to link individual AUDIT-C scores with consultations within the primary health care centers and hospitalizations within district hospitals, recording diagnosis for both fully and partially attributable alcohol-related conditions 13 .…”
Section: Discussionmentioning
confidence: 99%
“…During month 3 of the 18-month implementation period, the first six consecutive screen positive patients identified by each PHC provider will be invited to give their consent to complete two follow-up questionnaires, at six months and twelve months after the initial screening. The patient interviews will be used for quality control 126 , but not as a study outcome measure. The follow-up questionnaires will be the same as the baseline questionnaire and will be undertaken by the local academic unit by face-to-face or telephone interview.…”
Section: Protocolmentioning
confidence: 99%
“…In addition to supporting the feasibility and criterion validity of the SCORe, Vendetti et al [24] found that SAMHSA cohort 3 providers tended to adhere to evidence-based protocols, an important condition for investigating program effectiveness. Using the SCORe, 76 providers were observed performing 388 services in emergency departments/ trauma centers (ED/TC), hospital out-patient/ambulatory clinics (OP) and hospital in-patient (IP) settings.…”
Section: Methodological Innovationsmentioning
confidence: 99%
“…Fidelity ratings were conducted using a session content checklist [16] on approximately half (48.4%) of all SBIRT sessions. Fidelity ratings were completed on a rolling weekly basis, such that each study clinician received information during supervision about the ratings from one session during the prior week.…”
Section: Methodsmentioning
confidence: 99%